P0425MEMBRANOUS NEPHROPATHY IN TURKEY: TURKISH SOCIETY OF NEPHROLOGY GLOMERULER DISEASES (TSN-GOLD) DATABASE RESULTS. (6th June 2020) - Yildiz, Abdulmecit; Ulu, Memnune Sena; Oruc, Aysegul; Ucar, Ali Riza; Ozturk, Savas; Alagoz, Selma; Eren, Necmi; Kocyigit, Ismail; Koksal Cevher, Simal; Haras, Ali Burak; Sumnu, Abdullah; Arinsoy, Turgay; et al.
Abstract: Background and Aims: Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in the adult population. The aim of our study is to determine the demographic and clinical characteristics and biopsy findings of the patients diagnosed with MN in our country. Method: The study included 991 patients with renal biopsy who were followed in 47 nephrology clinics and enrolled in the database of Turkish Nephrology Primary Glomerular Diseases (TSN-GOLD) Working Group between May 1, 2009, and June 1, 2019. The demographic and clinical characteristics and biopsy findings of all patients included in the study were analyzed. Results: The mean age of patients included in our study was 46±14.8 years and the gender distribution was (M / F, 582/409). 80.3% (n = 796) of the patients had nephrotic proteinuria at the time of diagnosis. Before the biopsy, the PLAR2 antibody was examined in 137 patients and positive in 71.5% (n = 98) patients. Hypertension was present in 34.6% (n = 343) of the patients. Mean estimated glomerular filtration rate was 93.9±32.8 ml/min/1.73 m 2, albumin level was 2.7 ± 0.2 mg/dL, proteinuria level in urine was 7, 1±6, 4 gr/day and total cholesterol level was 295±3.7 mg/dL. On light microscopy, baseline membrane thickening was found in 92% (n=907) and interstitial inflammation in 53% (n=524) specimens. In immunofluorescence staining, 3 (+) IgG accumulation was highest in 578 (58.3%) of the specimen. Conclusion: This multicentre study is the largest study to analyze clinical, laboratory, and biopsy specimens of MN patients at the time of biopsy in our country. The findings are consistent with the literature. Prospective follow-up results of these patients will help us to understand the renal prognosis and treatment response better.